ANALISIS RETURN PORTOFOLIO YANG OPTIMAL PADA SAHAM LQ 45 YANG TERCATAT DI BURSA EFEK INDONESIA SELAMA PERIODE 2008-2010 - Jolanda Saputri; Oktafalia Marisa Muzammil (Business Management Journal, 2017)
This research aimed to analyze the optimal portfolio return and the change in IHSG to changes in stock prices the securities sector. The purpose of this study is the author wanted to determine the effect of the transaction value of the securities sector stock price changes. The method used is the Sharpe Model, Single Index Model, and using Microsoft Office Excel. The result of this research is the only portfolio on the agricultural sector able to generate a positive return. Conclusions of this research, there were 12 companies included in the the optimal portfolio in LQ45 and agricultural sectors only have return rate postitif of 19:16% and the risk by 5.92%. Keywords : Return, Risk, Single Indeks Model, and Sharpe Model